Atlas of Global Development : Third Edition - World Bank (World Bank, 2012)
Human and economic developments are closely linked to geography. The mission of the World Bank Group is to assist countries to overcome poverty and establish a sustainable path for their development. Providing reliable information about the state of the world and its people is an important part of that mission. Recognizing the formidable challenges and great successes that have been achieved should strengthen our resolve to work together to fight poverty and increase human welfare. To that end the World Bank has published an atlas for over 40 years. This edition of the Atlas of Global Development draws on a global database compiled from the work of the World Bank, other international agencies, and national statistical offices of member countries.